FACTORS RELATED TO QUALITY OF LIFE IN GARBAGE COLLECTORS IN BANGKOK METROPOLITAN - Kusuwan , Pattarachai; Sukonthasab, Suchitra (Journal of Sports Science and Health, 2025)
Purpose The objectives of this research were to study the factors related to the quality of life and to study the quality of life of garbage collectors performing their duties in the Bangkok metropolitan area. Methods The sample group consisted of 509 garbage collectors from district offices in 50 districts of Bangkok metropolitan. A random sample of 5% was taken from each district. Data collection was based on accidental sampling. The research tools included a questionnaire on predisposing factors, enabling factors, and reinforcing factors, as well as the short version of the World Health Organization Quality of Life Assessment Thai version (WHOQOL-BREF-THAI). Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The relationships between the variables were examined using Pearson’s product-moment correlation coefficient, with statistical significance determined at p≤0.05. Results The garbage collectors in Bangkok metropolitan had the highest level of predisposing factors and reinforcing factors, a moderate level of enabling factors, and an overall quality of life at a moderate level. When examining each component of quality of life, it was found that the garbage collectors demonstrated a good level of mental well-being, while their physical health, social relationships, and environmental aspects were at a moderate level. The analysis of the relationships between variables revealed that predisposing, enabling, and reinforcing factors were significantly correlated with the quality of life of Bangkok garbage collectors at the 0.05 level of statistical significance. Conclusion The garbage collectors in Bangkok metropolitan demonstrated a moderate level of overall quality of life. Predisposing, enabling, and reinforcing factors were found to be significantly associated with their quality of life. Moreover, the garbage collectors showed the highest levels of predisposing and reinforcing factors, while the enabling factors were observed at a moderate level.